Pemanfaatan Teknologi RESTFul Web Service pada Pengembangan Sistem Informasi Pencatatan Nilai Kelulusan PK2MABA di Fakultas Ilmu Komputer Universitas Brawijaya - Khairi Ubaidah; Issa Arwani; Dian Eka Ratnawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
New students orientation (PKKMB) is an activity carried out to help new students to be oriented towards new levels of education in college life. Faculty of Computer Science (FILKOM) Universitas Brawijaya through Article 27 Guidelines of regulations which obliges students to take part in the PKKMB series and makes student graduation from the PKKMB series a requirement to be able to measure the thesis exam. With the urgency related to the PKKMB passing status which is so crucial, an information system is needed to manage the PKKMB scores. However, the current condition of the PKKMB value management information system is still not optimal. Because the scores archiving process is done manually by sending it on the Google Sheets application page. In addition, the existing data is still not well organized, making it difficult to validate the PKKMB graduation status. From these problems, this research was carried out with the aim of recording information systems PK2MABA passing scores by utilizing RESTful Web Service technology. By using Laravel as a system development framework on the web platform and Lumen as a REST API development framework, the system has been developed and tested with the Blackbox testing method which produces a proportion of 100%, as well as testing the System Usability Scale with a value of 88.75 which means this system is in on a scale of value B with the category of Excellence.